2021
DOI: 10.1002/humu.24284
|View full text |Cite
|
Sign up to set email alerts
|

Molecular landscape of DYSF mutations in dysferlinopathy: From a Chinese multicenter analysis to a worldwide perspective

Abstract: Dysferlinopathy is one of the most common subgroup of autosomal recessive limbgirdle muscular dystrophies that is caused by mutations in DYSF gene. However, there is currently no worldwide comprehensive genetic analysis of DYSF variants. Through a national multicenter collaborative effort in China, we identified 222 DYSF variants with 40 novel variants from 245 patients. We then integrated DYSF variants from disease-related genetic databases including LOVD (n = 1020) and Clinvar (n = 1179), to depict the globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In this study, we reviewed the clinical and molecular characteristics of 26 Chinese patients with dysferlinopathy screened by immunohistochemistry and genetic analysis, and identified a high proportion of novel variants which expand the genetic spectrum of dysferlinopathy. Recently Zhong et al reported 245 dysferlinopathy patients in 2021, although, our data further supplemented their study [11] and emphasized the importance of differentiation from inflammatory myopathy.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…In this study, we reviewed the clinical and molecular characteristics of 26 Chinese patients with dysferlinopathy screened by immunohistochemistry and genetic analysis, and identified a high proportion of novel variants which expand the genetic spectrum of dysferlinopathy. Recently Zhong et al reported 245 dysferlinopathy patients in 2021, although, our data further supplemented their study [11] and emphasized the importance of differentiation from inflammatory myopathy.…”
Section: Introductionsupporting
confidence: 79%
“…The screening of DYSF variants was conducted as described previously [11,19] (transcript number NM_003494.4). Most of the clinical exome sequencing analysis were accomplished by MyGenosticsInc, Beijing, China.…”
Section: Genomic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…A wide range of DYSF mutations has been identi ed, including missense, nonsense, frameshift deletions/insertions, splice mutations, and large exonic deletions (9). The top three outcomes in the world patients dataset were missense (42.3%), splicing (13.7%), and frameshift (11.1%) (17). Missense mutations accounted for nearly half of the study in this cohort, and a comparison of the mutational spectrum with a large French cohort (37) suggested a possible difference, with null mutations being lower in the Chinese cohort (25% vs 76%), while missense mutations were more common in the Chinese cohort (43% vs 24%).…”
Section: Discussionmentioning
confidence: 99%